Demands for community libraries in crowdfunding campaigns in Southeast Brazil - Camillo, Everton da Silva [UNESP]; Oliveira Silva, Bruna Daniele de [UNESP]; Almeida Junior, Oswaldo Francisco de [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2022)
The study inquires as to whether Brazilian crowdfunding campaigns for community libraries are solely for the purpose of sustaining and maintaining them. The purpose of this paper is to show the demand for community libraries in Southeast Brazil's crowdfunding campaigns. Concurrently with the content analysis method, a lexicographical analysis was conducted using a Descending Hierarchical Classification. The chi-square test was used to test hypotheses. Along with supporting and preserving community libraries, crowdfunding campaigns aim at social and local development, increasing library infrastructure, people's access to cultural goods and educational activities, and the maintenance of social projects of broad impact in Southeast Brazil. The study suggests a public policy for community libraries to achieve their financial autonomy. Then the study concluded that community members can arrange logical acts that result in the extension of the debate over public policies for community libraries and, subsequently, in the organization of goals for the development of a documentary product arising from the discussions.
Keywords: community library; crowdfunding; public policies; collective actions; social participation